Systematic Literatur Review: Efektvitas Model Pembelajaran Terhadap Disposisi Matematika Siswa - Kartikasari, Euis Sri; Maharani, Anggita; Laelasari, Laelasari (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
Mathematics learning is not only important in developing cognitive abilities, but affective abilities are also very important. One of these affective abilities is mathematical disposition. Efforts to improve mathematical disposition need to be supported by effective learning models. So the aim of this research is to determine the effectiveness of the learning model on students' mathematical disposition. By using a literature study research method, namely the Systematic Literature Review (SLR) method, this research revealed that in the 2019-2024 period there were 101 relevant research articles related to the effectiveness of learning models on students' mathematical disposition abilities with the most widely used learning model being the learning model. Problem Based Learning (PBL) The most widely used research method is quantitative research methods (quasi-experimental) while the research subjects are mostly aimed at junior high school students.